Compensation for workers adversely affected by corporate restructuring: pension rights, the law and public policy - Clark, G (Routledge, 1993)
The costs of restructuring to corporations can be enormous. So too can be the costs of restructuring for workers and communities, layoffs, plant closings, and long-term unemployment are often the consequences of restructuring. Normally, those adversely affected by restructuring are not due any compensation other than short-term unemployment benefits. But in instances where corporations have illegally sought to shift the costs of restructuring to workers by selectively denying them their pension and benefit rights, US federal courts have held that compensation is possible. The question is, however, what is appropriate compensation, given legal entitlements and abstract theoretical notions of just compensation? This question is explored with reference to case studies of corporate restructuring in the US that have involved identified violations of the Employee Retirement Income Security Act of 1974. In this context, it is argued that current remedies and recipes for compensation are wholly inadequate when justice is delayed. After working through a series of different recipes for compensation, the paper closes with an analysis of the associated problems of enforcement and the protection of workers' pension rights.